Effect of ultrasound irradiation combined with ozone pretreatment on the anaerobic digestion for the biosludge exposed to trace-level levofloxacin: Degradation, microbial community and ARGs analysis. (15th May 2020) - Zhao, Qian; Li, Mei; Zhang, Kefeng; Wang, Ning; Wang, Kaikai; Wang, Hongbo; Meng, Shujuan; Mu, Ruimin
Abstract: Anaerobic digestion, the principal method of stabilizing biosolids in wastewater treatment plants (WWTPs), can efficiently and largely attenuate the antibiotic resistances in biosludge. This study aims to investigate the effect of oxidative pretreatment with ultrasound irradiation combined with ozone (US/O3 ) on the mesophilic and thermophilic anaerobic digestion (MAD and TAD) for the biosludge bearing trace fluoroquinolones contaminants-levofloxacin (LEVO) which was widely used in recent years. During the oxidation, the trace-level LEVO was almost completely degraded. The methanogenic activity in US/O3 pretreated TAD dosed 0.1 mg/L LEVO was much higher than those in single MAD and TAD, therefore leading to a remarkable increase in biogas production. The identification of levofloxacin intermediates during chemical degradation was analyzed using LCMS technique and the reaction pathway based on them was proposed. Hydroxyl radicals provided by US/O3 contributed to oxidative ring opening of LEVO as well as degradation of other biomacromolecules in the biosludge. Besides, the quinoline resistance genes- qnrA and qnrS declined significantly by 1–2 orders of magnitude in US/O3 -pretreated TAD, indicating that the active radicals produced by US/O3 oxidized and degraded LEVO and therefore inactivated the antibiotic resistant bacteria or genes in the biosolids. Meanwhile, the composition and structure of the microbial community altered and the diversity and richness of total bacterial and potential human pathogens decreased, the pattern of which was correlated with LEVO-resistant genes. Among the well-known AD-related phylum including Bacteroidetes, Firmicutes, Methanobacteria as well as Thermotogae which has been previously detected in TAD and performed organic hydrolysis and degradation, the potential LEVO-resistant bacteria were probably affiliated to Actinobacteria, Bacteroidetes, Proteobacteria, Thermotogae . This study revealed the contribution of US/O3 pretreatment to the anaerobic digestion in terms of ARGs reduction for trace-LEVO- exposed biosludge and could provide useful guidance for controlling the dissemination of ARB and ARGs in sewage sludge. Highlights: US/O3 facilitates the ozonation of LEVO and biomacromolecules in biosludge. US/O3 pretreatment and TAD improves biogas production by 30.0–33.2%. .OH fosters ring opening of LEVO by attacking unsaturated carbon-carbon bonds. Representative quinoline resistance genes in biosludge declined after US/O3 -TAD treatment. The potential ARB and resistant pathogens were identified for correctly handling biosolids.